The discursive construction of superintendent statesmanship on Twitter - Todd M. Hurst (Arizona State University, 2017)
The modern school superintendent fulfills a unique role in the U.S. public education system. He or she is structurally empowered as the de facto head of the local educational system, thereby granted with a certain amount of trust and authority regarding educational issues. At the same time, the superintendent is, in most cases, an employee of a politically appointed school board. While norms have traditionally encouraged superintendents to use caution with respect to political discourse (Boyd, 1974), social media has created a new platform upon which they can reach a broad range of stakeholders regarding many issues, including politics. This study seeks to better understand the emerging practice of political discourse by superintendents on Twitter. Employing discursive psychology principles (Potter Wetherell, 1992), I will analyze the political tweets of superintendents and position current practices in relation to established role conceptualizations of the position. Findings include that superintendents utilize Twitter as a tool to establish their positions as political insiders and as advocates for students.